Abdominal paracentesis drainage attenuates severe acute pancreatitis by enhancing cell apoptosis via PI3K/AKT signaling pathway - Chen Luo; Qilin Huang; Xiaohui Yuan; Yi Yang; Bing Wang; Zhu Huang; Lijun Tang; Hongyu Sun (Apoptosis, 2020)
Our previous studies have shown that abdominal paracentesis drainage (APD) is a safe and effective strategy for patients with severe acute pancreatitis (SAP). However, the underlying mechanisms behind APD treatment remain poorly understood. Given that apoptosis is a critical pathological response of SAP, we here aim to investigate the effect of APD on cell apoptosis in pancreatic tissues during SAP and to explore its potential molecular mechanism. SAP was induced by 5% sodium-taurocholate retrograde while APD group was inserted a drainage tube into the right lower abdomen of rats immediately after SAP induction. Histopathological staining, serum amylase, endotoxin and inflammatory mediators were measured. Cell apoptosis, apoptosis-related proteins and signaling pathway were also evaluated. Our results demonstrated that APD treatment significantly attenuated pancreatic damage and decreased the serum levels of amylase, endotoxin, TNF-α, IL-1 and IL-6 in rats with SAP. Notably, APD treatment enhanced cell apoptosis and reduced necrosis in pancreatic tissues, as evidenced by Tunnel staining, the increased pro-apoptosis proteins (Cleaved-caspase-3 and bax) and decreased anti-apoptosis protein (Bcl-2). Moreover, the effect of APD on cell apoptosis was further confirmed by the regulatory pathway of PI3K/AKT and NF-kB signaling pathway. These results suggest that APD attenuates the severity of SAP by enhancing cell apoptosis via suppressing PI3K/AKT signaling pathway. Our findings provide new insights for understanding the effectiveness of APD in patients with SAP.